2011
DOI: 10.1186/1471-2172-12-35
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between surfaces and soluble factors define the immunologic and angiogenic properties of myeloid dendritic cells

Abstract: BackgroundDendritic cells (DCs) are antigen presenting cells capable of inducing specific immune responses against microbial infections, transplant antigens, or tumors. Interestingly, microenvironment conditions such as those present in tumor settings might induce a DC phenotype that is poorly immunogenic and with the capability of promoting angiogenesis. We hypothesize that this plasticity may be caused not only by the action of specific cytokines or growth factors but also by the properties of the surfaces w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…The same might apply to studies with ECMp in a murine system, where bovine collagen I and vitronectin influenced the maturation of murine blood monocytederived iDC and caused higher IL-12p40 release, T cell activation, and proliferation. 44 However, it has also been reported, that murine bone marrow-derived DC were completely unresponsive to maturation stimuli after initial culture on collagen I, 25 which is consistent with our results. Whether the lack of iDC maturation demonstrated for all ECMp tested in our study will also result in reduced T cell proliferation within a mixed lymphocyte culture is not clear.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The same might apply to studies with ECMp in a murine system, where bovine collagen I and vitronectin influenced the maturation of murine blood monocytederived iDC and caused higher IL-12p40 release, T cell activation, and proliferation. 44 However, it has also been reported, that murine bone marrow-derived DC were completely unresponsive to maturation stimuli after initial culture on collagen I, 25 which is consistent with our results. Whether the lack of iDC maturation demonstrated for all ECMp tested in our study will also result in reduced T cell proliferation within a mixed lymphocyte culture is not clear.…”
supporting
confidence: 83%
“…24 Other groups demonstrated the influence of ECMp coating of biomaterials on the properties of mature DC. [25][26][27] Other APC types, such as B cells, 28,29 might be affected by the adjuvant activity of ECMp or even modulate the maturation and functions of DC. 30 Experimental data in the murine system demonstrated that ECMp could influence the differentiation, proliferation, or cytokine secretion pattern of B-1b cells.…”
mentioning
confidence: 99%
“…Historically, intercellular communication mechanisms responsible for mediating immune responses have focused on cell-to-cell and receptor–ligand mediated interactions (41) as well as soluble cytokines, chemokines, and angiogenic factors (42). Recently, EVs have emerged as novel mediators of intercellular communication composed of both exosome (30–100 nm) and microvesicle (100 nm–1 μm) subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that these cells exhibit high plasticity, being capable of acquiring angiogenic properties in vivo under pathological conditions (15). We hypothesized that this might be caused not only by the presence of specific cytokines or growth factors, but also by the interaction with different extracellular matrix (ECM) components as we have recently demonstrated (40). Taking into account this, we decided to determine the relevance of substrate adherence on the biology of myeloid(m) DCs.…”
Section: Resultsmentioning
confidence: 99%